IPTEKS SISTEM PENGENDALIAN INTERNAL PEMERINTAHAN PADA BADAN PERENCANAAN DAN PEMBANGUNAN DAERAH PROVINSI SULAWESI UTARA - Lintang, Franclin Alexandria; Mintalangi, Syermi (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
Badan Perencanaan dan Pembangunan Daerah (BAPPEDA) for North Sulawesi Province is a part of regional government agency that became an element of regional government planning in helping the Governor in terms of Plan & Execution of Regional Policies. They worked in research and planning for regional developments. In order to perform in managing its tasks and duties, BAPPEDA for Sulawesi Province has to build an internal control system within the organization, so it will promote an effective work performances in achieving BAPPEDA's visions and missions. Therefore, with the existence of Internal Government Control System thatÂ  regulated on Peraturan Pemerintah No. 60 Tahun 2008 - this become the guidance for government agency in making decisions and executions; to minimize the failure possibilities in managing the organisations and agencies.Keywords : Government, Internal Control System, Bappeda Sulut